(untitled) (Research, Society and Development, 2022)
This systematic review protocol aims to verify the existence of synergistic effect of phototherapy in tissues that received dermal fillers. The review will be carried out through the stages of preparation of the research question, search for primary studies, selection of studies according to eligibility criteria, data extraction, analysis, and synthesis of evidence. The question will be based on the PICOS strategy: “Does the combined use of dermal fillers and phototherapy have a synergistic effect on facial rejuvenation?” The search in the literature will be carried out in seven databases and in sources of gray literature. The results will be exported to the Rayyan application for the purpose of deleting duplicate studies. The reading of the titles and abstracts will be carried out by two independent and blind reviewers. Randomized clinical studies that associated phototherapy in tissues that received dermal fillers will be selected for full reading. The data will be extracted and submitted to a narrative synthesis, and if possible, the meta-analysis. In the methodological quality analysis, the RoB2 tool will be used for the risk of bias and the GRADE tool for the quality of evidence.